Spatial and temporal dynamics of bovine wealth in india: Implications on milk composition and growth - B, Sserunjogi; Kaur, Parminder (Indian Journal of Dairy Science, 2016)
The region-wise bovine population and milk production dynamics as well as bovine compositional changes in India’s four regions viz., Northern, Southern, Western and Eastern were analyzed. Compound annual growth rates were computed to study the growth trends in breed-wise population and milk production. Chow’s test was applied to study the impact of liberalization of livestock markets on bovine milk production growth between the Pre and Post-WTO periods. The study revealed that the adult female bovine population was largely dominated by buffaloes and crossbred cattle. Overall, the percentage share of in-milk adult females was greater than their dry counterpart in all censuses. The indigenous cattle population registered declining shares while the female crossbred cattle population registered impressive growth rates during the study period. The northern region possessed the highest shares of buffalo population in the last seven censuses. At the all India level, buffalo milk production, outnumbered crossbred and indigenous milk production in percentage and absolute terms. The eastern and western regions contributed the largest shares to indigenous milk production while the southern and western regions registered the highest growth rates in crossbred milk production in all inter-census periods. Among the milch animals studied, crossbred cattle had the highest lactating efficiency, followed by buffaloes in all the censuses and regions. The Chow’s F- test values were found significant for all regions indicating the large impact of liberalization policy on the growth rates of milk production in India. A regional based policy initiative encompassing improved technological intervention, breed improvement, quality feeds and fodder availability and adequate stocking rates to maintain ecological balance is needed to realize the full potential of livestock sector in India.